2002
DOI: 10.1046/j.1365-2842.2002.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HEMA on bonding of Er:YAG laser‐irradiated bovine dentine and 4‐META/MMA‐TBB resin

Abstract: The purpose of this study was to evaluate the priming effect of 2-hydroxyethylmetaclirate (HEMA) following acid treatment on resin bonding to prototype Er:YAG laser-irradiated dentine. Extracted bovine dentine following laser irradiation was acid treated by aqueous solution of 10% citric acid (10-0) or 10% citric acid/3% ferric chloride (10-3), and additionally treated with 35% HEMA. Pre-treated dentines were bonded to the polymethyl-methacrylate (PMMA) rod with 4-META/MMA-TBB resin (Super Bond C & B) and mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…The bonding strength of adhesives to Er:YAG laserirradiated dentine is lower than that to bur-cut dentine [11][12][13] . Dentine after Er:YAG laser-irradiation had a denatured surface structure 21,22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bonding strength of adhesives to Er:YAG laserirradiated dentine is lower than that to bur-cut dentine [11][12][13] . Dentine after Er:YAG laser-irradiation had a denatured surface structure 21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…When irradiated by Er:YAG laser pulses, the dentin surface becomes microscopically rough, and dentinal tubules are opened without smear layers 8,10) . Although these characteristics are considered to be advantageous for resin bonding, the bond strength of resin to Er:YAG laser-irradiated dentin is lower than that to conventionally ground dentin [11][12][13][14][15][16][17] . The formation of a hybrid layer is thought to be necessary for excellent resin-dentin bonding.…”
Section: Introductionmentioning
confidence: 99%
“…12,19 In order to irradiate uniformly, some studies employed laser irradiation with the dentine specimen fixed to a moving stage. 11,12,20 However, this study employed freehand irradiation, since our previous data indicated no significant difference between uniform irradiation using a moving stage and freehand irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Fixation of denatured layers by application of 5% glutaraldehyde, 19 or removal by application of 37% phosphoric acid and 10% sodium hypochloride have been proven effective in improving resin bond strength. 20,21 There is a greater possibility of irritation and inflammation of pulp with chemical procedures than with conventional methods of composite restoration, and very little is yet known about such pulp reaction to such chemical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This denatured layer, according to recent reports impairs restoration with composite resin by disturbing adhesion between the dentin and the composite resin. [5][6][7][8][9][10][11] It differs from non-irradiated dentin, both chemically and physically. 4,9,[12][13][14][15][16][17] These differences can be disadvantageous, as the denatured layer tends to be brittle and to break easily when subjected to bond strength tests after the Er:YAG-laser-irradiated dentin is filled with composite resin.…”
Section: Introduction Wmentioning
confidence: 99%